Peran Pendidikan Kewarganegaraan dalam Membentuk Karakter Peduli Lingkungan di Madrasah Ibtidaiyah Studi Tindakan Kelas - Aswan, Aswan (Yayasan Zia Salsabila, 2022)
This study examines the role of civic education in shaping environmentally conscious character in Madrasah Ibtidaiyah through a classroom action research approach. The problem raised is the lack of integration of civic values with environmental issues in learning, which can impact the low ecological awareness of students. The purpose of this study is to explore how civic education that incorporates environmental concepts can enhance students' character in caring for environmental sustainability. This study uses a qualitative method with a classroom action research approach, involving teachers and students in Madrasah Ibtidaiyah in Kendari City. Data was collected through observation, interviews, documentation, and teacher reflection, then analyzed descriptively. The results show that the integration of civic education and the environment in learning can increase students' ecological awareness and encourage them to engage in real actions, such as greening activities and waste management at school. As a result, the curriculum that incorporates environmental issues enriches students' understanding of citizenship and contributes to the formation of a more environmentally conscious student character. This study recommends further development of a curriculum based on the integration of civic education and environmental sustainability.